Return-to-elite competition for a football player after a Hodgkin lymphoma diagnosis. A case report study - Felipe, J. L.; Perez-Guerra, A.; Alonso-Callejo, A. (Science and Medicine in Football, 2025)
The aim of this case report was to evaluate the physical performance and capacity to return-to-elite competition of a male elite football player from the Spanish first division (LaLiga EA Sport™) after the diagnosis of a Hodkin lymphoma (HL). A 28-years-old elite football player (height 178.9 cm; weight 72.3 kg; VO2max 57.0 mL·kg-1·min-1) for the Spanish first division participated in this study. Before diagnosis with HL, he participated in 100 Official Matches (OM) in the Spanish second division (LaLiga Hypermotion™). Once discharged, 271 days after the diagnosis, patient played 5 OM in the Spanish second division (season 22/23) and 37 OM in the Spanish first division (LaLiga EA Sport) (season 23/24). After the placement of a reservoir-type central venous catheter and semen cryopreservation, he received Rituximab, Cyclophosphamide, Doxorubicin Hydrochloride, Vincristine Sulfate (Oncovin), and Prednisone every 21 days for a total of 6 cycles without complications and excellent tolerance. The player began the solo-training on 16th July 2022 until the progressive return to group training on 9th December 2022 and the full incorporation into the group was on 2nd January 2023. Player has not lost performance on his return-to-elite competition and has even improved in some variables (HSR). An adequate strategy in the initial stages during chemotherapy treatment, based on progressively resistance training (from Reps in Reserve 5 to 2) combined with High-Intensity Interval program (15% above the lactate threshold; Rate of Perceived Exertion 9) helps to achieve adequate Return-to-Play and Return-to-Performance values without any loss of performance when return-to-elite competition.